An intensive culture of common carp, Cyprinus carpio in indoor biofloc system - Reza Akrami (تغذیه آبزیان, 2022)
Biofloc technology is an environmentally aquaculture production system in which nutrients are continuously recycled and reused. In this technology, growth performance, water quality and production costs need to be considered. The objective of this study was to evaluate intensive culture of common carp (Cyprinus carpio) in indoor biofloc system (BFT). One biofloc treatment with minimum water exchange and one control with 30% renewal water in triplicates were managed. Fish (40 g in weight) were stocked in 400 L fiberglass tanks at a density of 2 kg/m3 and 18-week experiment was conducted. Mollasses was added to the biofloc tanks at a C:N ratio of 20:1. In this study, biofloc treatment exhibited significantly higher mean total ammonia, nitrite, nitrate, alkalinity, total suspended solid and lower pH than the control (p<0.05). Growth parameters and final biomass did not differ significantly between BFT and control. Feed conversion ratio was higher (p<0.05) in the control than in the BFT treatment. Water consumption/kg common carp produced in the control was 12 times higher than in the BFT group. It can be concluded that farming common carp in BFT system is more economic in saving great amount of feed and water with minimal discharge of pollutants without negative effects on carp growth.